ANALISIS KEBIJAKAN KOPI ROBUSTA DALAM UPAYA MENINGKATKAN DAYA SAING DAN PENGUATAN REVITALISASI PERKEBUNAN - Suwandari, Anik; Soetriono, Soetriono (Jurnal Sosial Ekonomi Pertanian, 2010)
The research concerning Robusta coffee policy has been carried out in Sidomulyo Village, Silo District, Jember Regency. The resylt of the research shows that : (1). The peopleâs coffee farming has competitive and comparative excellence; (2). The governmentâs policy to the tradable input has positive impact whereas to the non tradable input has negative impact; (3). The increasing of import tariff in 10 % and 15 % can cause the in creasing of domestic price of coffee, while the decreasing of import tariff in 5 % causes the decreasibg of domestic price of coffee, so this condition has negative impact for the peopleâs coffee farming and positive impact for coffee industries; (4). The higer the value of rupiahs (in 10 % ang 15 %) becomes the lower the price of tradable social input and tradable coffee output has, as a result the comparative excellence of poople coffee farming tends to be lower; (5). The lowers the value of rupiahs (in 5 %) becomes the higher the price of tradable social input and tradable coffee output has, as a result the comparative excellence of peopleâs coffee farming tends to be higher; (6). The plantation revitalization especially Robusta coffee farming and agribusness can be done by looking for special market, inventing new business, changing the rules by using information technology, and revitalizing agribusiness institution especially cooperation. So that is way the government has to decide a flexible policy of import tariff of coffee.Key words : Policy; Competitive; Revitalization.